Intrapulmonary Pharmacokinetics and Pharmacodynamics of Itraconazole and 14-Hydroxyitraconazole at Steady State - Conte, John E. (American Society for Microbiology, 2004)
We determined the steady-state intrapulmonary pharmacokinetic and pharmacodynamic parameters of orally administered itraconazole (ITRA), 200 mg every 12 h (twice a day [b.i.d.]), on an empty stomach, for a total of 10 doses, in 26 healthy volunteers. Five subgroups each underwent standardized bronchoscopy and bronchoalveolar lavage (BAL) at 4, 8, 12, 16, and 24 h after administration of the last dose. ITRA and its main metabolite, 14-hydroxyitraconazole (OH-IT), were measured in plasma, BAL fluid, and alveolar cells (AC) using high-pressure liquid chromatography. Half-life and area under the concentration-time curves (AUC) in plasma, epithelial lining fluid (ELF), and AC were derived using noncompartmental analysis. ITRA and OH-IT maximum concentrations of drug (C(max)) (mean ± standard deviation) in plasma, ELF, and AC were 2.1 ± 0.8 and 3.3 ± 1.0, 0.5 ± 0.7 and 1.0 ± 0.9, and 5.5 ± 2.9 and 6.6 ± 3.1 μg/ml, respectively. The ITRA and OH-IT AUC for plasma, ELF, and AC were 34.4 and 60.2, 7.4 and 18.9, and 101 and 134 μg · hr/ml. The ratio of the C(max) and the MIC at which 90% of the isolates were inhibited (MIC(90)), the AUC/MIC(90) ratio, and the percent dosing interval above MIC(90) for ITRA and OH-IT concentrations in AC were 1.1 and 3.2, 51 and 67, and 100 and 100%, respectively. Plasma, ELF, and AC concentrations of ITRA and OH-IT declined monoexponentially with half-lives of 23.1 and 37.2, 33.2 and 48.3, and 15.7 and 45.6 h, respectively. An oral dosing regimen of ITRA at 200 mg b.i.d. results in concentrations of ITRA and OH-ITRA in AC that are significantly greater than those in plasma or ELF and intrapulmonary pharmacodynamics that are favorable for the treatment of fungal respiratory infection.